Reforming global banking rules: Back to the future? - Ranjit Lall (Danish Institute for International Studies (DIIS), 2010)
One of the most significant casualties of the recent fi nancial crisis has been the Basel II Accord, a set of proposals to regulate the international banking system drawn up by a committee of G10 banking supervisors between 1999 and 2004. Whether or not they view Basel II as a direct contributor to the crisis, policymakers agree that the fundamental tenets of the accord have been decisively discredited by recent events. In this paper, I ask why Basel II's creators fell so short of their aim of improving the safety of the international banking system - that is, why Basel II failed. Drawing on recent work on global regulatory capture, I present a theoretical framework which emphasizes the importance of timing and sequencing in determining the outcome of rule-making in international fi nance. Th is framework helps to explain not only why Basel II failed, but also why the latest set of proposals to regulate the international banking system - the so-called 'Basel III' Accord - is likely to meet a similar fate.
Keywords: 330; Basel II; Eigenkapitalvorschriften; Bankenpolitik; Welt